Formulasi Tablet Mengandung Ekstrak Daun Sirsak, Ekstrak Kulit Buah Manggis dan Ekstrak Jamur Ling Zhi serta Uji Aktivitas sebagai Antioksidan dan Imunomodulator - SWASONO R. TAMAT; ELIZA RAHMAN; LEONARDUS B.S. KARDONO (Fakultas Farmasi Universitas Pancasila, 2014)
Investigation on formulation of film coated tablets containing combination of three active substances, i.e. extracts of soursop leaf, mangosteen rind and Ling Zhi mushroom has been carried out, which was expected to have high antioxidant and immunomodulator activities. The research consists of formulation of film coated tablets F1 containing extracts of soursop leaf-mangosteen rind-Ling Zhi mushroom (100:100:125 mg) and F2 (125:75:125 mg) in each 840 mg tablet. Full examination showed that film coated tablet F1 and F2 comply with the 4th Indonesian Pharmacopoeia, except for the dissolution test. Determination of antioxidant activity with DPPH method showed IC50 of F1 tablet was 215.93 μg/mL, IC50 of F2 tablet was 363.86 μg/mL, whereas IC50 of soursop leaf extract 602.64 μg/mL, IC50 of mangosteen rind extract 111.80 μg/mL and IC50 of Ling Zhi mushroom extract 2199.50 μg/mL. Determination of immunomodulatory activity by in vivo carbon clearance method showed a moderate phagocytic index of 1.385 for F1 tablet, 1.469 for F2 tablet, and <1 for Echinacea extract as positive control. Stability test performed based on the α-mangostin content showed that the shelf-life of F1 tablet was 1.865 years, and F2 tablet was 1.842 years. The result showed that film coated tablet F1 and F2 have both synergistic antioxidant and immunomodulatory activities as compared to their respective single extract. The result showed that the antioxidant activity and stability of film coated F1 tablet is better than F2 tablet, but the imunomodulatory activity of F2 tablet is better than F1 tablet.